The Analysis of Conversational Implicatures and Directness Level of Politeness in Comic Strips - Jaufillaili Jaufillaili (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2017)
In this research paper, the writer intends to analyze the conversational implicatures and directness level of politeness in comic strips. The data are taken randomly from Art&Chip Sansom’s The Born Loser comic strips published in The Jakarta Post newspapers during June–July 2015. The objectives of this research are; (1) to analyze how the implicatures are creating the humorous effects of the jokes, and (2) to analyze how the directness level of politeness is described in the comic strips. This is a qualitative research, therefore it uses descriptive method with two theories; Grice’s Theories of Conversational Implicatures, and House and Kasper’s Theories of Directness Level of Politeness. Data collection is through library research and the writer analyzes the data based on the theories mentioned above.Keywords: conversational implicatures, directness level of politeness, comic strips